Book Review: Stefan Kozłowski, Przyszłość ekorozwoju, KUL, Lublin 2005 - Pawłowski, Lucjan (Problemy Ekorozwoju, 2006)
Another publication of prof. Kozłowski is an very comprehensive compendium of knowledge about sustainable development, unique on the Polish publishing market.